In situ loading of skin dendritic cells with apoptotic bleb-derived antigens for the induction of tumor-directed immunity - Ruben, Jurjen M (Oncoimmunology, 2014)
The generation and loading of dendritic cells (DC) ex-vivo for tumor vaccination purposes is laborious and costly. Direct intradermal (i.d.) administration of tumor-associated antigens could be an attractive alternative approach, provided that efficient uptake and cross-presentation by appropriately activated skin DCs can be achieved. Here, we compare the efficiency of i.d. delivery of relatively small apoptotic blebs (diameter ∼0.1–1 μm) derived from MART-1 transduced acute myeloid leukemia (AML) HL60 cells, to that of larger apoptotic cell remnants (ACR; 2–10 μm) in a physiologically highly relevant human skin explant model. Injection of either fluorescently-labelled ACRs or blebs alone did not affect the number or distribution of migrated DC subsets from skin biopsies after 48 hours, but resulted in a general up-regulation of the co-stimulatory molecules CD83 and CD86 on skin DCs that had ingested apoptotic material. We have previously shown that i.d. administration of GM-CSF and IL-4 resulted in preferential migration of a mature and highly T cell-stimulatory CD11(hi)CD1a(+)CD14(−) dermal DC subset. Here, we found that co-injection of GM-CSF and IL-4 together with either ACRs or blebs resulted in uptake efficiencies within this dermal DC subset of 7.6% (±6.1%) and 19.1% (±15.9%), respectively, thus revealing a significantly higher uptake frequency of blebs (P < 0.02). Intradermal delivery of tumor-derived blebs did not affect the T-cell priming and T(H)-skewing abilities of migratory skin DC. Nevertheless, in contrast to i.d. administration of ACR, the injection of blebs lead to effective cross-presentation of MART-1 to specific CD8(+) effector T cells. We conclude that apoptotic bleb-based vaccines delivered through the skin may offer an attractive, and broadly applicable, cancer immunotherapy.